Animal Simulation in Under/Post Graduate Studies: It's Effect in Clinical Pharmacology Research - Asis Bala (Open Journal of Pharmacology and Pharmacotherapeutics - Peertechz Publications, 2015)
Animal experimentation was successfully taken an important part of the curriculum of the students of medicine, pharmacy, nursing, dentistry, veterinary, and even to basic sciences like life sciences, zoology etc . The objective of the animal experiments was to develop skills for performing in-vivo experiments and to correlate the findings with theoretical concepts as well as in vitro results with prior permission to Committee for the Purpose of Control and Supervision of Experiments on Animals (CPCSEA). However by considering the seriousness of declining of wild life, the University Grant Commission (UGC) decided to stop the animal experimentation for both the under and post graduate levels and noticed accordingly [1]. Therefore redundant animal experiments are now trying to replace with the Computer Assisted Learning (CAL), animal simulation (AS; using Ex. Pharm, Ileum Ink software etc) or by molecular studies in cell culture. And the world wide acceptance of CAL and AS was documented in some of previous studies [2-6]. And finally UGC has also decided to bans use of animals for research in laboratories [7].